PENGARUH KARAKTERISTIK PEKERJAAN DAN MODAL PSIKOLOGI TERHADAP KINERJA DENGAN MOTIVASI SEBAGAI MEDIASI DAN BUDAYA ORGANISASI SEBAGAI MODERASI (Studi pada Sekretariat Daerah Kabupaten Rembang) - Nasikhah, 1352020019; Abdul Rozak, Hasan (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study is to analyze the effects of job characteristics and psychological capital on the job performance with motivation as mediator and organization culture as moderator in Rembang District Secretariat Apex . The population in this study is the civil service of Rembang District Secretariat Apex that amounts to 208 people. This study use purposive sampling and it was given 109 people .This study using statistical tests that include validity test with factor analysis, reliability test using Cronbachs alpha, double regression analysis, and significance test using the coefficient of determination to prove the validity of hypothesis and for mediation tests and also moderation tests. The results of this study correctly proved that the influence of job characteristics, psychological capital and motivation is positive and significant to job performance . Mediating test proved that the effects of job characteristics and psychological capital on the job performance are not mediated by motivation . Moderating test proved that the effect of psychological capital on the job performance is moderated by organization culture but also moderating test proved that the effect of job characteristics and motivation on the job performance are not moderated by organization culture. Keywords : job characteristics, psychological capital, motivation, job performance and organization culture.